Problem delokalizacji w rozszerzonej Unii Europejskiej - przyczyny i konsekwencje odpływu kapitału do Chin - Boba, Katarzyna (Delocalization Problems in the Extended European Union - Reasons and Consequences of a Capital Outflow into China, 2008)
In the age of progressive globalization one can observe a new phenomenon in the European Union, namely an interest of the EU countries in direct investment in other countries. The process is named "production delocalization" and concerns changes in production fragmentation and thus influences transformations in the economic structures. It must be emphasized that relocation of industry, services, etc. has been present in the world economy for many years. It is obvious that it is caused by increasing competition and is related to the need of production cost cut. The goal of this article is an analysis of delocalization problem in the extended European Union. The author is looking for the reasons behind this process. Consequences of outflow of direct investment streams into China are shown in the paper. The author makes an attempt to answer the question if production delocalization into China is dangerous for the EU economy. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 28, s. 25-38